Josh - Shigeru Chiba; Kiyoshi Nakagawa (Proceedings of the 3rd international conference on Aspect-oriented software development, 2004)
BACKGROUND: Low health literacy is a barrier to positive health behaviors and outcomes among adolescents, especially in marginalized communities. Sustained, youth-centered interventions for high-risk populations are limited. CONTRIBUTIONS TO PRACTICE: We implemented and conducted an exploratory evaluation of a year-long, medical student-led program for ninth- and tenth-grade students at two Detroit public high schools. The program demonstrated the feasibility of interactive school-based health literacy programming and identified practical considerations for future implementation. Using anonymous pre and postprogram surveys, we examined group-level response patterns in self-reported confidence on health-related knowledge and abilities (n = 71 baseline; n = 52 follow-up). Survey items reflected domains addressed during program sessions, including healthcare navigation, understanding medical terminology, identifying reliable health information, self-advocacy in healthcare settings, and emergency response skills. Postsurvey responses showed more favorable group-level response patterns across all domains. IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: Near-peer, school-based health literacy interventions may represent a practical strategy to support adolescent engagement with healthcare concepts in under-resourced communities. Partnerships between medical schools and secondary schools may provide scalable opportunities for community engagement and health education. CONCLUSIONS: This exploratory evaluation supports the potential value of medical student-led health literacy programming as a community-centered model for adolescent health education.